Rural Water Governance : Governance Model for Fulfilling Rural Drinking Water Needs in Indonesia - Putri Rut Elok Kurniatin; Irfan Ridwan Maksum (Universitas Medan Area, 2022)
Water Governance in meeting rural drinking water needs in the policy framework of the PAMSIMAS Program is strongly influenced by the project structure and mechanism from the central and local governments through Community Direct Assistance and Rural SPAM development grants. The researchers used a post-positivist approach with literature review method to analyze the policy direction of the governance model for meeting rural drinking water needs in Indonesia after the end of the program in 2021 through Gieseke governance perspective and compared it with data from the implementation of program policies. shows a shift in the governance model based on the analysis of the style of governance and governance actors. Analysis of the literature review and data shows that the governance of community-based rural drinking water needs requires special arrangements for its institutional forms, ownership of facilities and infrastructure, technical management, and drinking water quality test. Meanwhile, the complexity of drinking water governance results in rural drinking water governance model trilemma. The trilemma faced by the Government in constructing village governance model indirectly leads to Meta Governance model that is capable to combine the governance models and emerge a new situation.